Food wars! Shokugeki no soma. Volume 6, Memories of battle - Tsukuda, Yuto, 1989- (Shonen Jump advanced., 2015)
The chosen participants of the Totsuki Institute's annual Fall Classic begin their training, but as they do, someone special visits Polaris Dorm.